2019
DOI: 10.1016/j.peh.2019.100150
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ego depletion or mental fatigue on subsequent physical endurance performance: A meta-analysis

Abstract: Highlights-Ego depletion and mental fatigue impair subsequent endurance performance-The duration of the mental effort task doesn't predict the magnitude of impairment-The effect is higher on isolation than whole-body tasks-The effect is higher when the person-situation fit is low-This effect should not be seen only through the "fatigue" prism but also as "value"

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(145 citation statements)
references
References 93 publications
(96 reference statements)
11
126
7
1
Order By: Relevance
“…These conclusions seem to stand in contrast with those of two previous meta-analyses conducted in this domain Giboin & Wolff, 2019). performed a meta-analysis based on a similar literature search strategy, except for the fact that their inclusion criteria also considered tasks shorter than 30 mins.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…These conclusions seem to stand in contrast with those of two previous meta-analyses conducted in this domain Giboin & Wolff, 2019). performed a meta-analysis based on a similar literature search strategy, except for the fact that their inclusion criteria also considered tasks shorter than 30 mins.…”
Section: Discussioncontrasting
confidence: 72%
“…In general, the reported effect sizes seem to become closer to zero over the years. This trend is significant in the dataset analyzed by , b1 = -0.04, SEb = 0.01, z = -3.11, p = .002, and non-significant for Giboin and Wolff, b1 = -4 Some peculiarities of the meta-analyses conducted by and Giboin and Wolff (2019) prevent the use of the 3-parameter selection model to test for publication bias. Both meta-analyses collated data from studies with within-participants designs and between-groups designs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A substantial body of evidence supports the ego depletion concept (Cunningham & Baumeister, 2016). On the behavioral level, a multitude of studies has shown that ego depletion leads to impaired performance in a broad range of subsequent self-control demanding tasks (for meta-analyses, please see Giboin & Wolff, 2019;Hagger et al, 2010). On the experiential level, applying self-control leads to perceptions of exertion (Milyavskaya, Inzlicht, Johnson, & Larson, 2019;Wolff et al, 2019), thereby attesting to the implied costliness of exerting self-control (Baumeister et al, 1998).…”
Section: )"mentioning
confidence: 98%